Simulation study of mixed pressure and flow control systems for optimal operation of centrifugal pumping plants - Gevorkov, Levon; Rassõlkin, Anton; Kallaste, Ants; Vaimann, Toomas (Electrical, Control and Communication Engineering, 2018)
A Simulink/DriveSize based model for the mutual pressure and flow control of a centrifugal pumping plant with a variable speed drive is proposed. The model provides the possibility of power calculation during both throttling and speed control and to estimate the optimal working point according to these calculations. The model is developed to provide the possibility of power reduction during pressure and flow maintenance with the help of mixed pressure control strategy. To evaluate the system, a series of experiments have been conducted. After the validation of the proposed model through testing, which proved that the designed system is more beneficial from the power consumption point of view than the traditional pressure control methods, it can be stated that the system is useful for pressure and flow control optimization of the centrifugal pumping plants